Use of complete clearance for assessing treatment efficacy for 5-fluorouracil interventions in actinic keratoses: how baseline lesion count can impact this outcome. Issue 1 (1st January 2020) - Ezzedine, Khaled; Painchault, Caroline; Brignone, Melanie
ABSTRACT: Background : Many trials in actinic keratoses (AK) use complete clearance rate (100% reduction in number of lesions) as the primary endpoint. We explore limitations (predominantly baseline factors) associated with this outcome. Objective : This analysis assessed the effect of baseline lesion count on complete clearance rate using randomized controlled trials (RCTs) that evaluated 5-fluorouracil (5-FU) formulations, alone or with 10% salicylic acid solution, in patients with AK. Methodology : Correlation between baseline lesion count and complete clearance rate at week 8 was assessed using Pearson's coefficient. Results : Five RCTs assessing 5-FU (4%, 5%, or 0.5% in 10% salicylic acid solution) in 1, 080 patients with AK were included. Mean lesion count at baseline ranged from 8.1 to 21.2 lesions per patient. Complete clearance rate was negatively associated with number of lesions at baseline. Correlation between mean number of lesions at baseline and complete clearance rate was strong (r 2  = 0.94) and statistically significant (p < 0.001). Conclusion : This analysis showed that, in a homogenous set of trials, complete clearance rates achieved with 5-FU interventions are inversely related to number of lesions at baseline. These findings highlight the limits of restricting treatment evaluation to complete clearance rate and the relevance of alternative measures.